Dynamics-induced charge transfer in semiconducting conjugated polymers - Bauch, Fabian; Dong, Chuan-Ding; Schumacher, Stefan (Journal of Materials Chemistry C)
Dynamics-induced interchain charge transfer in a polymer aggregate in stack configuration can be understood by single-oligomer polaron energy.